A comparative study of the police officer views on policing during the COVID-19 pandemic in the United States. Issue 1 (27th September 2021) - Maskály, Jon; Kutnjak Ivkovich, Sanja; Neyroud, Peter
Abstract : Purpose: This study adds to the developing literature on how coronavirus disease 2019 (COVID-19) affected policing. Unlike prior research, which focused on police agencies, the authors focus on the perceptions and experiences of police officers. Specifically, about changes in workload or activities during the peak of the pandemic compared to prior to the pandemic. Additionally, officers report on changes in potential second-order effects resulting in changes from the pandemic. Design/methodology/approach: The data come from the survey responses of 167 police officers from seven police agencies of various sizes from around the USA. The authors assessed mean level differences between organizations using a general linear model/ANOVA approach and report a standardized effect size. Findings: There is a considerable heterogeneity in police officers' perceptions of organizational and operational changes made by their police agencies in response to the COVID-19 pandemic. The results show that perceptions of some changes were more strongly by the agency than were others. The study's results show there are substantive differences in how police officers from different police agencies viewed these operational and organizational changes (i.e. between agency differences). Most of the variance was primarily explained by differences between police officers within the same agency (i.e. within organization differences). Originality/value: This study moves beyond the monolithic approach to studying how the pandemic affected the police agency and moves to asking officers about their experiences with these changes and the second-order effects of these changes.